Effect of Narrowband Interference on Galileo E1 Signal Receiver Performance. (20th December 2011) - Zhang, Jie; Lohan, Elena-Simona
Abstract : Satellite navigation technology is becoming essential for civil application. The high-accuracy navigation service is demanded. However, the satellite signal may be exposed to the signal from other systems, which are sharing the same frequency band. This is a potential threat for the performance of navigation devices. The aim of this paper is to present an interference impact assessment in the context of global navigation based on the new modulation Composite Binary Offset Carrier (CBOC) that will be used for Galileo E1 civil signal. The focus is on the analysis of the Galileo CBOC-modulated signal robustness against narrowband interference.